Homosexuelle im Nationalsozialismus. Neue Forschungsperspektiven zu Lebenssituationen von lesbischen, schwulen, bi-, trans- und intersexuellen Menschen 1933 bis 1945 - Schwartz, Michael (Zeitgeschichte im Gespräch, 2014)
How did homosexual, bisexual, transsexual, and intersexual persons live during the Nazi era? What persecutory measures did they face? This compendium addresses these and other questions. A focus is placed on the police and justice system as well as political, administrative, and social repression.